Are SMEs meeting the challenge of integrating e-commerce into their businesses? A review of the development, challenges and opportunities. (21st June 2006) - Pool, Patricia W.; Parnell, John A.; Spillan, John E.; Carraher, Shawn; , Donald L. Lester
While e-commerce technology has spread rapidly throughout large firms in the developed world, growth among Small and Medium-sized Enterprises (SMEs) has not been as pervasive. This paper discusses the current state of e-commerce development in SMEs, outlines challenges faced by many SMEs and proposes several options for e-commerce integration. Specific opportunities in the areas of customer service and relationship management, supply chain management and e-commerce support are discussed.